Urban planning as an enabler of urban health: Challenges and good practice in England following the 2012 planning and public health reforms. (May 2019) - Carmichael, Laurence; Townshend, Tim G.; Fischer, Thomas B.; Lock, Karen; Petrokofsky, Carl; Sheppard, Adam; Sweeting, David; Ogilvie, Flora
Highlights: Current land development process hinders the consideration of health in planning. Public health evidence must be translated into actionable healthy planning principles. The economic case for healthy design is needed to challenge assumptions made within developers' 'viability' assessments. Local planning policies can help thwart the private sector weakening standards. Cross sector partnership and capacity building are key resources of healthy planning. Abstract: This article synthesises the challenges faced by the English (urban) spatial planning system to become an enabler of urban health and explores some keys features of the evidence base, policy tools and policy implementation issues that urban planners need to be aware of to become health enablers. It draws on good practice identified in an Economic and Social Research Council (ESRC) seminar series involving over 500 academic researchers and practitioners between 2015 and 2017. A number of key recommendations emerged out of the project. First, planning and health agendas must align at the local level. Second, the evidence base of health priorities must be locally relevant. Third, robust tools can support the creation of frameworks for delivering health outcomes through planning. And finally, adequate resources are necessary to develop the capacity of key place-making stakeholders.